Critical Event Checklists to Manage Perioperative Critical Events Using High-Fidelity Simulation - Lisa Cunningham; Pamela Morgan; Deborah Tregunno; Tobias Everett; Jordan Tarshis (Association of American Medical Colleges, 2015)
Abstract This resource contains eight high-fidelity simulation scenarios designed for operating room teams to manage critical events. These scenarios were developed to simulate one of eight critical events for which critical event checklists have been developed. The purpose of this educational module is to allow other facilities to use these scenarios to permit their teams to practice the management of eight specific critical events with and without the use of a critical event checklist. Debriefing templates and scripts are included for the eight scenarios to guide others in the conduct of the debriefing. Evaluations of the performance of the teams are done using two tools, one of which involves the adherence to key processes determined by evidence-based data and expert consensus. The second tool examines the nontechnical skills aspects of the team performance. Included in this resource are the patient's history, physical exam, and laboratory findings, as well as the actual scenario and how it should unfold. Also included are a description of the aids for surgical simulation, PowerPoint orientation presentation, confidentiality forms, mannequin and lab orientation, instructor's guide, citation details for the critical event checklist and the team emergency assessment measure tools, simulation interest group scenario templates, debriefing scripts, and exit questionnaire. The teams that completed these educational sessions had a very positive reaction. On the exit questionnaire, the participants (n = 35) rated the following statements (1 = strongly disagree, 5 = strongly agree): "Managing these simulated scenarios will improve my performance in a similar clinical situation" (Mdn = 5), "The debriefing session helped identify gaps in my practice and to clarify important issues" (Mdn = 5), "The information that I learned about critical perioperative events is relevant and beneficial to my practice" (Mdn = 4), "This session will help me to practice more safely in an ambulatory surgical facility" (Mdn = 4), "Critical event checklists are helpful to deal with critical events in an ambulatory surgical facility" (Mdn = 4), and "Critical event checklists should be available in an ambulatory surgical facility" (Mdn = 5).